Impact of tumour RAS/BRAF status in a first-line study of panitumumab + FOLFIRI in patients with metastatic colorectal cancer - Karthaus, Meinolf; Hofheinz, Ralf-Dieter (British journal of cancer, 2016)
Background:To investigate tumour biomarker status and efficacy of first-line panitumumab+FOLFIRI for metastatic colorectal carcinoma (mCRC).Methods:154 patients received first-line panitumumab + FOLFIRI every 14 days. Primary end point was objective response rate (ORR). Data were analysed by tumour RAS (KRAS/NRAS) and BRAF status, and baseline amphiregulin (AREG) expression.Results:Objective responses occurred more frequently in RAS wild type (WT) (59%) vs RAS mutant (MT) (41%) mCRC and in RAS WT/BRAF WT (68%) vs RAS or BRAF MT (37%) disease. Median response duration was longer in RAS WT (13.0 months) vs RAS MT (5.8 months) (hazard ratio (HR): 0.16). Median progression-free survival was longer in RAS WT vs MT (11.2 vs 7.3 months; HR, 0.37) and was also longer in RAS WT/BRAF WT vs RAS or BRAF MT (13.2 vs 6.9 months; HR, 0.25). Incidence of adverse events was similar regardless of RAS/BRAF status, and no new safety signals were noted. Among patients with RAS WT tumours, ORR was 67% with high AREG expression and 38% with low AREG expression.Conclusions:First-line panitumumab+FOLFIRI was associated with favourable efficacy in patients with RAS WT and RAS WT/BRAF WT vs MT mCRC tumours and was well tolerated.
Gesehen am 28.05.2019